DEVELOPING ENGLISH SPEAKINNG MATERIALS BASED ON CONTEXTUAL TEACHING AND LEARNING FOR GRADE TEN SENIOR HIGH SCHOOL AT SMA NEGERI 20 MEDAN - Tiurmaida Silitonga; Sri Minda Murni; Rika Rika (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
The objective of this study was to develop the speaking materials in Showing Care and Congratulation for the tenth grade students at SMA Negeri 20 Medan. The study was educational Research and Development (R & D). The data were gathered by distributing questionnaires to 30 students of SMA Negeri 20 Medan and administering interviews to the teacher. The result of the study was a set of developed teaching speaking materials based on CTL entitled “Meet and Speak” Which consists of two chapters on the topic of (1) Don’t be Sad My Friend and (2) Good Job. Each topic consists of Let’s Remember, Let’s Try, Let’s Use, Let’s Cooperate and Let’s Share. Keywords: Contextual Teaching and Learning, Supplementary, Speaking, RnD